Analisa Pengaruh Sambungan Mekanik Tipe Double Lap Terhadap Kekuatan Tarik Pada Komposit Polyester Serat Batang Pisang - Sugiarto, Bayu (2016)
This study aims to determine the influence of tensile strength and drilled holes printed on polyester composite mechanical connection type double lap on banana stem fibers. And to determine the effect of fiber volume fraction of 5% in the area around the hole on the connection type double lap Composite manufacture begins with the preparation of materials to be used are polyester resin, hardener, fiber banana tree trunks. After the first process of cutting and peel bark banana stems in layers to three from outside, then continue pressing process so that the inner bark of banana easily removed until the remaining fiber outer part, after it was cut and inserted into the PVC pipe that has been filled with water and then cpntinued the process of immersion for 1 month to be easy when taking fiber. Initial drying is done in a room without light eye day for 1 day. Furthermore, alkali treatment 2% KMnO4 for 2 hours followed drying at room without light the eyes. Manufacture of composites by hand lay-up method of fiber ratio ± 30% with preparing fiber inserted in an oven at a temperature of 310C hinga kadr water reaches 12% to 15% then the fiber is taken and arranged parallel. Tensile test to determine the tensile strength and maximum force that occurred in the hole, and the macro image of composite polyester fiber connection banana stems. From the test results show that the maximum force the specimen connection composites manufacture of holes drilled without determine fv and after the addition of fv 5% experienced a progressive increase of 218.874 N being 228.200 N, whereas for specimen hole printed without the addition of fv and after the addition of fv 5% of 288.252 N be 598.914 N. Further more, in the case of macro image pull-out fiber in the composite specimens drilled holes and printed.